(untitled) (Journal of the College of Basic Education, 2023)
The research discussed the features and characteristics of parametric architecture and how to use it as inputs for the design of contemporary architecture. The research started from defining what is parametric and parametric thinking and how to adopt engineering formulas and mathematical algorithms in designing architectural structures. By defining the relationship between the principles of mathematics and computer software in the production of design ideas based on the principles of the golden ratio, paper geometry and natural fractal to be inputs in the process of producing design ideas for fashion design. Hence, the focus was on what parametric structures are and how to adopt them to be structural elements different from the design recognized in fashion design, and to determine the nature and characteristics of parametric fashion design by focusing on the characteristics of non-stereotyping, flexibility and three-dimensional structure. The nature of the design adoption was determined by adopting the formulas of convergence and participation in the formation of products that satisfy the current consumer. A number of conclusions were reached, and they discussed the convergence and divergence in parametric design systems between architecture and fashion design.